Metabolic adaptation of Chlamydia trachomatis to mammalian host cells. Issue 6 (31st January 2017) - Mehlitz, Adrian; Eylert, Eva; Huber, Claudia; Lindner, Buko; Vollmuth, Nadine; Karunakaran, Karthika; Goebel, Werner; Eisenreich, Wolfgang; Rudel, Thomas
Summary: Metabolic adaptation is a key feature for the virulence of pathogenic intracellular bacteria. Nevertheless, little is known about the pathways in adapting the bacterial metabolism to multiple carbon sources available from the host cell. To analyze the metabolic adaptation of the obligate intracellular human pathogen Chlamydia trachomatis, we labeled infected HeLa or Caco‐2 cells with 13 C‐marked glucose, glutamine, malate or a mix of amino acids as tracers. Comparative GC‐MS‐based isotopologue analysis of protein‐derived amino acids from the host cell and the bacterial fraction showed that C. trachomatis efficiently imported amino acids from the host cell for protein biosynthesis. FT‐ICR‐MS analyses also demonstrated that label from exogenous 13 C‐glucose was efficiently shuffled into chlamydial lipopolysaccharide probably via glucose 6‐phosphate of the host cell. Minor fractions of bacterial Ala, Asp, and Glu were made de novo probably using dicarboxylates from the citrate cycle of the host cell. Indeed, exogenous 13 C‐malate was efficiently taken up by C. trachomatis and metabolized into fumarate and succinate when the bacteria were kept in axenic medium containing the malate tracer. Together, the data indicate co‐substrate usage of intracellular C. trachomatis in a stream‐lined bipartite metabolism with host cell‐supplied amino acids for protein biosynthesis, host cell‐provided glucose 6‐phosphate for cell wall biosynthesis, and, to some extent, one or more host cell‐derived dicarboxylates, e.g. malate, feeding the partial TCA cycle of the bacterium. The latter flux could also support the biosynthesis of meso‐2, 6‐diaminopimelate required for the formation of chlamydial peptidoglycan. Abstract : In a bipartite metabolism the obligate intracellular human pathogen Chlamydia trachomatis uses host cell derived amino acids and glucose‐6‐phosphate for feeding protein biosynthesis and cell wall biosynthesis, respectively. Host dicarboxylates, e.g. malate are used for supplementing the chlamydial partial TCA cycle and may support peptidoglycan formation.